The conundrum of motherhood: house helps and the mediated motherhood discourses in Kenya - Gladys Muasya (Communicare)
The globalised media tend to influence the content of local and regional media. This study sought to find the nature of mediated mothering discourse in Kenya and the extent to which it promoted the hegemony of intense mothering discourse; vis-a-vis indigenous mothering discourses such as co-mothering found among the collectivistic cultures of sub-Saharan Africa. Most workingclass mothers employ caregivers – house helps to mind their children. A total of 71 stories from 2009 to 2022 related to mothering were collected from two leading newspapers in Kenya – Daily Nation and The Standard – which feature lifestyle issues. These stories were analysed using inductive coding and constant comparison to identify categories. Findings show that most of the discourses were the extent to which mothers were allowed to pursue personal ambitions in relation to the needs of their children (have-it-all), the level of delegation of core mother duties to the house helps, and the quality of caregiving that was associated with good mothers. There was no consensus on the level of delegation permitted as both extremes were highly criticised. Mothers were not yet ready to co-mother with the house helps – showing the hegemony of mediated intense mothering discourse.